Impact of CD34+ cell dose on reduced intensity conditioning regimen haploidentical hematopoietic stem cell transplantation. (6th October 2019) - Salas, Maria Queralt; Atenafu, Eshetu G.; Bautista, Maria Rhida; Prem, Shruti; Lam, Wilson; Datt Law, Arjun; Shaibani, Zeyad‐Al; Kim, Dennis Dong Hwan; Michelis, Fotios V.; Lipton, Jeffrey Howard; Viswabandya, Auro; Mattsson, Jonas; et al.
Abstract: Objectives: Haploidentical hematopoietic stem cell transplant (haplo‐SCT) has been associated with higher rates of graft rejection, and a higher dose of CD34+ cell dose is frequently requested. We aim to explore the impact of CD34+ cell dose in peripheral blood stem cell (PBSC) grafts using reduced intensity conditioning (RIC) in haplo‐SCT. Methods: Sixty‐eight consecutive haplo‐SCT in adult patients were included. Graft‐vs‐host disease (GVHD) prophylaxis consisted on ATG, PTCy, and CsA. The cohort was divided in two groups using CD34+ dose of ≥ 9 × 10 6 CD34+/Kg as cutoff point. Median follow‐up was 8.9 months. Results: Median cell dose infused was 9.32 × 10 6 CD34+/Kg. Forty (58.8%) recipients received grafts with CD34+ cells ≥9 × 10 6 /kg. The infusion ≥ 9 × 10 6 CD34+/Kg cell dose had a negative impact in overall survival ( P  = .03) after adjusting for age at transplant. The cumulative incidence of acute GVHD and graft failure were not significantly influenced per CD34+ cell dose. Only four recipients had grade III aGVHD, and all of them received grafts with a CD34+ cell dose ≥ 9 × 10 6 . Conclusion: In RIC haplo‐SCT, recipients may not benefit from PBSC grafts with a CD34+/kg cell dose higher than 9 × 10 6 cells/kg, as it can have an adverse impact in post‐transplant outcome.